1996
DOI: 10.1073/pnas.93.23.13054
|View full text |Cite
|
Sign up to set email alerts
|

Double strand breaks at the HIS2 recombination hot spot in Saccharomyces cerevisiae

Abstract: Double strand breaks (DSBs) have been found at several meiotic recombination hot spots in Saccharomyces cerevisiae; more global studies have found that they occur at many places along several yeast chromosomes during meiosis. Indeed, the number of breaks found is consistent with the number of recombination events predicted from the genetic map. We have previously demonstrated that the HIS2 gene is a recombination hot spot, exhibiting a high frequency of gene conversion and associated crossing over. This paper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 27 publications
3
40
0
Order By: Relevance
“…At the ARG4 locus, however, DSB formation is inhibited by overlapping transcription (29). The cases of DSBs occurring in the coding regions of GLK1 and HIS2 genes (9,20) show that DSB inhibition by transcription through a gene can be overcome. Still to be elucidated is whether the formation of DSBs within coding regions is controlled by internal specific sequences or by distant cis-acting elements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the ARG4 locus, however, DSB formation is inhibited by overlapping transcription (29). The cases of DSBs occurring in the coding regions of GLK1 and HIS2 genes (9,20) show that DSB inhibition by transcription through a gene can be overcome. Still to be elucidated is whether the formation of DSBs within coding regions is controlled by internal specific sequences or by distant cis-acting elements.…”
Section: Discussionmentioning
confidence: 99%
“…(i) Most DSB sites are found located in intergenic regions containing transcriptional promoters (reviewed in ref. 1) but the occurrence of DSBs at other locations has been reported, including within the coding sequence of the HIS2 gene (9) and at uncharacterized positions in several artificial constructs (10). (ii) The occurrence of DSBs is controlled by determinants of chromatin structure, as they occur in regions that are hypersensitive to DNaseI and micrococcal nuclease (8,(10)(11)(12)(13).…”
mentioning
confidence: 99%
“…Cervantes et al (2000) showed that double-strand break formation is strongly reduced in a rec7 mutant. This is also the case in mutants of REC114, the homologous early recombination gene of S. cerevisiae (Pittman et al 1993;Bullard et al 1996). S. cerevisiae rec114 mutants and other early recombination mutants undergo meiosis I earlier than wild type.…”
Section: ) Many Mutants Are Available In Both Species Tomentioning
confidence: 90%
“…rec102, rec104, and rec114 (Bullard et al 1996); mre2 rec7 gene disruption: Two gene disruption mutations were constructed (Figure 1) 1977). Individual chromosomes can be traced used to transform strain SA2 to Ura ϩ by the lithium acetate through meiosis by the use of appropriate markers and method (Ito et al 1983 menting ade6-M210/ade6-M216 colonies are white.…”
Section: ) Many Mutants Are Available In Both Species Tomentioning
confidence: 99%
“…Chromosome III hotspot probes were derived from pME1210 (YCR048w) (Woltering et al 2000) and pNH90 (HIS4/ LEU2) (Hunter and Kleckner 2001). The chromosome VI hotspot (HIS2) was detected using pH 21 (Bullard et al 1996) (provided by Bob Malone) and the chromosome VIII hotspot (ARG4) used pMJ77 (provided by Michael Lichten). The mek1-as allele in pJR2 was constructed by subcloning a 3.2-kb EcoRI/ SalI fragment from pB131-Q241G (Niu et al 2009) into EcoRI/ SalI-digested Ylp5 (Parent et al 1985).…”
Section: Plasmidsmentioning
confidence: 99%